An Investigation into Macro-proliferation of some Selected Bamboo Species of Assam - Dubey, R. M.; Das, P. S.; Choudhury, Reeta (Indian Forester, 2008)
A new, easy and low cost technique has been developed for production of quality planting stock of B. vulgaris var. vittata, B. balcooa, B. bambos, B. nutans, B. tulda and D. hamiltanii vegetatively through two noded culm cutting with macro-proliferation which yields planting stock with survival rate of 90-100 %. Through this simple technique from a single bamboo node 60 to 180 nos. of bamboo saplings (propagules) can be produced in a year (April to March) depending upon the species selected. The best part of the technique is that it can produce bamboo planting stock round the year without involving many technicalities.